Is ecotourism an inexhaustible source of wealth? Recommendations for its sustainability - Carrascosa López, Conrado (2015)
Ecotourism can be defined as tourism based on nature and its protection. It represents a small share of tourism but has made great progress recently. This progress is closely associated with a progressive generalized environmental awareness. Costa Rica has an exuberant natural heritage and biodiversity, its main source of income is tourism, and has been a pioneer in the development of ecotourism for over thirty years. It is important to review this development to see what aspects can be improved. Since its birth in Costa Rica, there are certain aspects that must be corrected to prevent to exhaust this model. In this article, the question of whether ecotourism is inexhaustible will be answered; several reasons are given in the following lines. A deep review of the academic literature on ecotourism has been done, multiple ecotourism projects have been studied in Costa Rica and elsewhere in Latin America to know about their recent status, and their main concerns and difficulties. This paper concludes with some recommendations to improve ecotourism’s sustainability.